Perspectives of Hospital Pharmacists Towards Biosimilar Medicines: A Survey of Polish Pharmacy Practice in General Hospitals - Pawłowska, Iga (BioDrugs, 2019)
INTRODUCTION: There has been a significant increase in the volume of biosimilar medicines recently due to the expiries of patent protections of biologic medicines. Biosimilars are considered new medicines, and their usage in therapy is often associated with uncertainty from the perspectives of physicians, pharmacists and patients. OBJECTIVES: The purpose of this study was to identify hospital pharmacist opinions towards these new medicines and investigate their usage in practice. METHODS: A paper-based, self-administered questionnaire was distributed to Polish hospital pharmacists. RESULTS: Biosimilars were used in 77% of surveyed hospitals, whereas originator biologics were utilised within 90% of settings. The former medicines were found to consist of less than one-third of the entire course of biological pharmacotherapy used within Polish hospitals. A total of 88% of hospital pharmacists were concerned that the new drugs were not identical with the biologic versions, 48% with their immunogenicity and 44% with other pharmacokinetic properties. The majority of respondents (87%) stated that the most important advantage of biosimilars related to decreased costs. Furthermore, according to participants, pharmacist-led substitution is not appropriate. CONCLUSION: Due to the numerous concerns relating to the usage of biosimilars, their introduction into patient therapy requires special attention from healthcare providers. While pharmacists involved in the distribution of biosimilars are conscious of their impact in decreasing costs of therapy, they do not feel comfortable in recommending their substitution without a physician’s permission. There is a need for more precise legal regulations relating to biosimilars, improved communication between physicians and pharmacists, as well as educational initiatives to improve the safe and effective usage of biosimilars.